TINJAUAN YURIDIS TERHADAP PUTUSAN PRAPERADILAN NOMOR 05/PID/PRA/2014/PN.PBR - Berton Lowis Maychel; Erdianto '; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Investigators conduct an investigation of the evidence carefully and thoroughly. if after investigation was the lack of evidence, no proof, no evidence, or even light not criminal cases, the police investigators may issue a Warrant Termination of Investigation (SP3). Warrant termination of investigation, in case No. 05 / Pid / Pra / 2014 / PN.Pbr which tells the story of a villager Asmi Nur, Nur Asmi reported Br. Hj. Eva Yuliana, wife of the regent of Kampar regency with his friends named Br. Very Inspire and Br. Ral Mulyadi suspected of committing criminal offenses as listed in Article 170 of the Code of Penal namely Whosoever openly and jointly use violence against people or goods.Construction law pretrial decision No. 05 / Pid / Pra / 2014 / PN.Pbr is a case against termination case investigation by the Riau Police. Applicant named Nurasmi aged 36 years, occupation housewife, located at street Pematang Kulim districts Eastern Kampar Kampar Riau. The defendant is kapolda Riau is located at Jalan Sudirman Pekanbaru. The case started around June 2014. At that time, Nur Asni and Jamal were working on the land in the village Birandang, Kampar, attended Eva, Jeffery Noer and some aides. At the site had been a debate for Eva claiming the cultivated land is hers. The result is argue with each other and allegedly led to the beating. Because of the incident, the victim was rushed to Arifin Ahmad Pekanbaru. When treated, the victim is known to experience some bruises and claimed traumatized because aide found herself at gunpoint by the regent. Nur Asmi has made a police report but then the Riau Police issuing SP3 so Nur Asmi pretrial seeked. The judges' verdict is declared cessation of pretrial investigation of the case No: S.TN/54/X/2014/Reskrimum on termination of the investigation on 10 October 2014 was unlawful, ordered the defendant to continue the process of investigation of the case No: LP / 123 / VI / 2014 / Videos / Res Kampar dated June 1, 2014.Follow-up conducted by the Riau Police on pretrial decision No. 05 / Pid / Pre / 2014 / PN.Pbr is to do with the reopening of cases of alleged maltreatment again this. Investigators will conduct the investigation back in. The witnesses will be called again and questioning.Key words: pretrial-SP3